Transumbilical Balloon Atrial Septostomy with Echocardiographic Monitoring - Sudigdo Sastroasmoro; Bambang Madiyono; Ismet N. Oesman; Sukman Tulus Putra; Eva Jeumpa Soelaiman (Indonesian Pediatric Society, 1988)
Balloon atrial sept ostomy is usually necessary for survival beyond infancy in patients with transposition of the great arteries and insufficient intracardiac mixing. Since the umbilical vein and ductus venosus are often patent in the newborn infants, this route can be considered as an alternative to a femoral venous route in a critically ill infant. A 7 day-old newborn with D-transposition with intact ventricular septum and small patent foramen ovate was successfully managed by creating atrial septal defect through transumbilical balloon arterial septostomy. The procedure was carried out in the neonatal intensive care unit, guided by 2D-echocardiography. The arterial oxygen saturation increased dramatically upon the completion of the procedure, and a large atrial septal defect could be demonstrated echocardiographically. Unfortunately the infant died before further definitive surgery was performed.